Transnational Memories. (26th September 2014) - Assmann, Aleida
Abstract : The 'transnational turn', which is challenging bounded views on national belonging, also opens up promising perspectives for memory studies. It fosters a rethinking and reconfiguring of national memories in the context of transnational connectedness. My sketch of seven types of transnational memories points to different empirical contexts in which states, politicians, jurists, activists, artists and scholars go beyond national borders and interests to conceptualise new forms of belonging, solidarity and cultural identification in a world characterised by streams of migration and the lingering impact of traumatic and entangled pasts.